1991
DOI: 10.2514/3.23402
|View full text |Cite
|
Sign up to set email alerts
|

Review of propulsion applications and numerical simulations of the pulsed detonation engine concept

Abstract: Here we review experimental and computational studies of the pulsed detonation engine concept (PDEC) and present results of our recent numerical study of this concept. The PDEC was proposed in the early 1940s for small engine applications; however, its potential was never realized due to a complicated, unsteady operation regime. In this study, we demonstrate the use of current advances in numerical simulation for the analysis of the PDEC. The high-thrust/engine volume ratio obtained in our simulations demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
28
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(28 citation statements)
references
References 16 publications
0
28
0
Order By: Relevance
“…It has also been suggested that increasing the combustion chamber size relative to the engine size will help with the very short residence times [3]. In a review paper, Roy et al [4] reported the typical length for a pulse detonation engine is 0.3-3 m. We believe this 8 cm pulsejet is the smallest operational pulsejet reported [5][6][7][8]. The fuel injection system, combustion chamber, and the inlet geometry must be carefully designed to create a fast mixing process and the necessary fluid dynamic and acoustic time scales to permit pulsejet operation.…”
Section: Introductionmentioning
confidence: 91%
“…It has also been suggested that increasing the combustion chamber size relative to the engine size will help with the very short residence times [3]. In a review paper, Roy et al [4] reported the typical length for a pulse detonation engine is 0.3-3 m. We believe this 8 cm pulsejet is the smallest operational pulsejet reported [5][6][7][8]. The fuel injection system, combustion chamber, and the inlet geometry must be carefully designed to create a fast mixing process and the necessary fluid dynamic and acoustic time scales to permit pulsejet operation.…”
Section: Introductionmentioning
confidence: 91%
“…4,6,7 These promising results have led to many PDE applications being proposed. For example, it has been suggested that PDEs can be used as cost-effective replacements for small gas-turbine engines, as potential replacements for combustors on existing large-scale gas turbines, or as thrust augmenters.…”
mentioning
confidence: 95%
“…Our knowledge of detonations is almost exclusively based on propagating waves and almost all of the discussion about steady detonation wave engines is pure speculation. In this paper, the focus will be on steady waves although it should be pointed out that propagating detonations have been proposed as components in intrinsically unsteady wave engines (Eidelman et al 1991, Voytsekhovskiy et al 1964.…”
Section: Introductionmentioning
confidence: 99%